OXIDES AS HETEROGENEOUS PROMOTERS FOR LIQUID-PHASE HYDROCARBONYLATION REACTIONS WITH IODOCARBONYLRUTHENIUM CATALYSTS - Braca, G.; Galletti, AMR; Sbrana, G.; Trabuco, E. (Amer Chemical Soc, 1992)
Basic or acid oxides, used as heterogeneous promoters of carbonylruthenium catalysts in liquid-phase hydrocarbonylation reactions on oxygenated substrates, strongly affect the activity and selectivity of the catalytic system. Concurrent or successive reactions of simple carbonylation, homologation, hydrogenation to hydrocarbons, and etherification take place to varying extents. Carbonylation and etherification are favored by acid oxides and homologation and hydrogenation by basic oxides. This behavior is related to the formation and stabilization by the oxides of H+ and H- hydridocarbonylruthenium catalytic species, whose relative concentrations in solution depend on the nature of the oxide. Heterogeneous oxides are easily separated and recycled from the reaction mixture. Their use simplifies the catalytic system and allows one to direct the catalytic process toward the target product.